Validation of a perceptions of care adjective checklist. - Redshaw, M; Martin, C (2009)
BACKGROUND: This study describes the psychometric characteristics, validity and reliability of the revised version of the perceptions of care adjective checklist (PCACL-R) with women who had recently given birth. Data were collected from a national survey of women's experiences of maternity care (n = 2960). METHODS: Internal consistency, predictive validity, convergent validity, discriminant validity and confirmatory factor analyses were applied to the data. RESULTS: Confirmatory factor analysis revealed an excellent fit to a bi-dimensional structure entirely consistent with the negative and positive valencing of adjectives in the measure, supporting the use of the instrument as a two subscale tool comprising positive and negative subscales. The PCACL-R revealed good convergent validity against measures of satisfaction with care and excellent divergent validity characteristics assessed against duration of labour. Discriminant validity was assessed against measures of area-based maternal deprivation, partner status and type of delivery. These analyses revealed commendable discriminant validity of the PCACL-R. Internal consistency characteristics of the positive and negative subscales of the PCACL-R were acceptable. The predictive validity of the PCACL-R was also found to be excellent. CONCLUSION: The PCACL-R is consequently recommended as a valid, reliable, respondent acceptable and easy to administer instrument to assess women's experiences of their care during labour and childbirth. The measurement characteristics of the PCACL-R suggest that the tool could be incorporated into both clinical and research contexts with confidence. The checklist terms used are applicable to other phases of maternity care and indeed to a wide range of health care contexts. Exploratory use in with other user groups is recommended.